Face-to-Face and Virtual Instruction Practices in Nepali Schools (Panauti Journal, 2023)
The COVID-19 pandemic affected the education sector along with the other sectors in Nepal. The education system and its major components have been disrupted by the pandemic. In this regard, I have prepared a research article to explore the status and practice of face-to-face and virtual instruction in school education in Nepal.The first objective of this paper is to assess the present situation of the face-to-face mode of schooling. The second objective is to analyze the current state of virtual learning and the third objective is to study the change from face-to-face and virtual learning in the education system. This research is qualitative one. This is delimited in the secondary schools of the Gorkha Municipality. I have selected the schools of the study area purposively. I have used non-participant observation, focus group discussion, and open-ended interviews to generate information and it was the primary source. The COVID-19 pandemic has created an alternative mode of instruction, i.e., a virtual mode. I have found that depending solely upon the virtual mode of instruction during the COVID-19 pandemic situation has been less effective in the study site due to poor internet access and electronic devices. The blended approach has been more effective in the instructional process.